Expert C# 5.0 with .NET 4.5 framework - Rahman, Mohammad (Expert's voice in .NET., 2013)
Expert C# 5.0 is a book about getting the best from C#. It's based on the principle that to write good, high-performance, robust applications you need to understand whats going on deep under the hood. If you are already experienced with writing managed applications and want to learn more about how to get the best from the language at an advanced level, then this is the book for you. Expert C# 5.0 discusses the familiar C# language in forensic detail. Examining familiar elements closely to reveal how they really work. Key language features that you are already familiar with, such as Enums, Strings and Collections, are teased apart and examined under the twin microscopes of MSIL (Intermediate Language) and the Windbg debugger to see what's really going on behind the scenes as your code is compiled and passed to the CLR. This unparalleled depth of explanation will help you to become a true master of the C# language and architect better crafted applications that work in the most efficient and reliable way possible. It will also give you the insight you need to rapidly identify and fix the stubborn coding faults that others may be unable to diagnose.